2014
DOI: 10.1016/j.ydbio.2013.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cell polarity in the cartilage growth plate and perichondrium of metacarpal elements by HOXD13 and WNT5A

Abstract: The morphology of bones is genetically determined, but the molecular mechanisms that control shape, size and the overall gestalt of bones remain unclear. We previously showed that metacarpals in the synpolydactyly homolog (spdh) mouse, which carries a mutation in Hoxd13 similar to the human condition synpolydactyly (SPD), were transformed to carpal-like bones with cuboid shape that lack cortical bone and a perichondrium and are surrounded by a joint surface. Here we provide evidence that spdh metacarpal growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
69
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 47 publications
3
69
0
1
Order By: Relevance
“…Here we show a direct link between Hox function and Wnt signaling; a theme that is reminiscent of a recent report of loss of Wnt2/2b expression in the mesenchyme of Hox5 triple-mutant lungs during development (Hrycaj et al, 2015). Another recent study examining Hoxd13 function in digit development reported that Hoxd13 promotes expression of Wnt5a in vitro (Kuss et al, 2014). All Hox proteins bind to the same (ATTA) binding sequence, and therefore it is plausible that Wnt5a is a direct target of Hox proteins during development.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Here we show a direct link between Hox function and Wnt signaling; a theme that is reminiscent of a recent report of loss of Wnt2/2b expression in the mesenchyme of Hox5 triple-mutant lungs during development (Hrycaj et al, 2015). Another recent study examining Hoxd13 function in digit development reported that Hoxd13 promotes expression of Wnt5a in vitro (Kuss et al, 2014). All Hox proteins bind to the same (ATTA) binding sequence, and therefore it is plausible that Wnt5a is a direct target of Hox proteins during development.…”
Section: Discussionsupporting
confidence: 81%
“…This study adds to growing evidence that Hox function in the mesoderm of several organ systems plays region-specific roles associated with the establishment of proper Wnt signaling crosstalk during organogenesis (Kuss et al, 2014;Hrycaj et al, 2015). A more complete elucidation of mesodermal-endodermal crosstalk during development of the pancreas is crucial to the enhancement of ex vivo protocols for generating functional β-cells as a cellular therapy for the treatment of diabetes.…”
Section: Discussionmentioning
confidence: 77%
“…Originally discovered in Drosophila melanogaster, PCP signaling polarizes cells in the plane of epithelia of many tissues, including the eye, wing, abdomen and thorax (Adler, 2002;Das et al, 2002;Lawrence et al, 2004;Shimada et al, 2001;Strutt, 2001;Tomlinson and Struhl, 1999). In vertebrates, Wnt/PCP signaling is known to polarize both epithelial and mesenchymal tissues (Gray et al, 2011) and has been implicated in many cellular processes, such as C&E gastrulation movements, polarization of ciliary structures, neurulation, cartilage morphogenesis and stem cell expansion (Borovina et al, 2010;Bradley and Drissi, 2011;Kuss et al, 2014;Le Grand et al, 2009;Mahaffey et al, 2013;Wada and Okamoto, 2009;Wallingford et al, 2000;Zilber et al, 2013). Genetic studies in Drosophila led to the identification of several core PCP components, including the four-pass transmembrane protein Van Gogh (Vang; also known as Strabismus), the seven-pass transmembrane proteins Frizzled (Fz) and Flamingo (Fmi; also known as Starry night) and the cytoplasmic proteins Dishevelled (Dsh, or Dvl), Diego (Dgo) and Prickle (Pk) (Adler et al, 1997;Chae et al, 1999;Gubb et al, 1999;Taylor et al, 1998;Theisen et al, 1994;Usui et al, 1999;Vinson and Adler, 1987;Wolff and Rubin, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This co-optation of key developmental functions to accompany the evolution of paired limbs was initially observed for the HoxD cluster (Dolle et al 1989;Lewis and Martin 1989), which, together with the HoxA cluster (Haack and Gruss 1993;Yokouchi et al 1995b), is critical for the formation of the proximal and distal pieces of our arms and legs (Davis et al 1995;Fromental-Ramain et al 1996;Kmita et al 2005). While the exact function of HOX proteins during limb development remains to be fully assessed, they seem to be involved in the control of bone growth (Zákány and Duboule 1996;VillavicencioLorini et al 2010;Gonzalez-Martin et al 2014;Kuss et al 2014) in both complementary and redundant manners (references in Zakany and Duboule 2007).…”
mentioning
confidence: 99%